2006
DOI: 10.1007/s10534-006-9036-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic exposure to cadmium on prostate lipids and morphology

Abstract: Cadmium is an environmental toxic metal implicated in human prostate carcinogenesis. The mechanism of its toxicity is not fully understood. Previously, we showed that cadmium exposure induces oxidative stress, especially lipid peroxidation. This study evaluates the effect of chronic exposure to 0.886 mM of cadmium (Cd) per liter in the drinking water on prostate lipid content and metabolism in Wistar rats. We determined the lipid profile and measured the expression of lipogenic enzymes: FAS, GPAT, LPL, DGAT-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 48 publications
2
20
0
1
Order By: Relevance
“…Cd was found to dose-dependently down-regulate the plasma and erythrocyte concentrations of cholesterol, triacylglyceride and phospholipids the brain concentrations of cholesterol and triacylglyceride with a concomitant increase in phospholipids concentrations and decrease hepatic cell concentrations of cholesterol and phospholipids with a concomitant up-regulation in triacylglyceride concentrations significantly compared to control animals. These were in agreement with the findings of other researchers [23][24][25][26]. The data also indicate that the activity of MDA an end product of lipid peroxidation was up-regulated as a result of Cd-induction which is in consistent with previous researchers [24].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Cd was found to dose-dependently down-regulate the plasma and erythrocyte concentrations of cholesterol, triacylglyceride and phospholipids the brain concentrations of cholesterol and triacylglyceride with a concomitant increase in phospholipids concentrations and decrease hepatic cell concentrations of cholesterol and phospholipids with a concomitant up-regulation in triacylglyceride concentrations significantly compared to control animals. These were in agreement with the findings of other researchers [23][24][25][26]. The data also indicate that the activity of MDA an end product of lipid peroxidation was up-regulated as a result of Cd-induction which is in consistent with previous researchers [24].…”
supporting
confidence: 93%
“…Several interpretations of these results could be considered. Firstly, the decrease in cholesterol may be due to inhibition of lecithin-cholesterol acyltransferase activity in Cd-treated rats [23,24]. Secondly, the cholesterol decreases in Cd-exposed animals suggests that Cd activates the acyl-CoA: cholesterol acyltransferase which catalyzes intracellular esterification of cholesterol and as such is involve in intestinal absorption of cholesterol hepatic assembly of ApoBcontaining lipoproteins foam cell formation and atherogenesis [27].…”
Section: Discussionmentioning
confidence: 99%
“…It adversely affects many of the body's tissues, including bone [30]- [32]. The importance of nutritional supplements such as phytochemicals on lowering the harmful effects of Cd on the liver and kidney had been reported [29] [33].…”
Section: Discussionmentioning
confidence: 99%
“…PSA is normally present in blood at low level, the desirable level of PSA that is considered normal in men is less than 4ng/ml [12]. Previous reports have shown that PSA level is increased in heavy metal toxicity [13,14]. The significantly raised PSA concentration in the ewaste exposed group in this study may be linked to a trend towards metal-induced oxidative stress and the associate initiation of carcinogenesis caused by the effects of heavy metals on the prostate tissue.…”
Section: Discussionmentioning
confidence: 45%